Pengaruh Komunikasi Interpersonal dan Disiplin Kerja Terhadap Kinerja Karyawan Tunas Toyota Cabang Bekasi - Rica Erliyana Wijaya; Zahara Tussoleha Rony; Rycha Kuwara Sari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The research aims to determine the influence of interpersonal communication and work discipline on the performance of Tunas Toyota Bekasi branch employees. This research uses a quantitative type of research. The technique for taking this research uses a non-probability sampling method with a saturated sampling technique (census) where in this method the entire employee population is used as a sample, namely 85 employees at the Bekasi branch of Tunas Toyota. The data analysis method for this research uses multiple linear regression. The data was processed using IBM SPSS statistics 25. The results of this research show (1) interpersonal communication has a significant effect on the performance of Tunas Toyota Bekasi branch employees. (2) work discipline has a negative effect on the performance of Tunas Toyota Bekasi branch employees. And (3) interpersonal communication and work discipline influence simultaneously or together on the performance of Tunas Toyota Bekasi branch employees.